Pt Deendayal Upadhyaya’s Integral Humanism Swarajya and Surajya - S. Sepeya, Rashmeesh (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
In India, the current government of Bhartiya Janta Party is following the path laid down by Pt. Deendayal Upadhyaya through his philosophy of Integral Humanism during 1960s. He was of the opinion that problems of mankind can be solved by adopting integrated holistic approach. Paper throws light on his concept of Integral humanism, Swarjya and Surajya.